O processo comunicacional do clichê cinematográfico em filmes de terror slasher - Silva, André Campos (Universidade do Vale do Rio dos Sinos, 2014)
The research aim problematize the use of cliché in film , considering it as a communication process that helps contribute to understanding the form and content of the films . The focus of the study is on the clichés present in the slasher subgenre of horror, through connections with the archetype of the shadow. Three basic conceptual axes organize work: horror movies, fashion and aesthetic content, the construction process of the characters and narratives of horror movies. The few specific studies on the clichés in movies led us to the use of authors from various aspects, among them are researchers in the field of communication and audio visual as Eco, McLuhan, Xavier, Aumont, Bordwell. Also participated in the theoretical construction of narrative as Candido, Mckee, Fields, Field. The field of philosophy in its connection with the aesthetic aspect was also important to Kant, Burke and Szondi. The empirical research took place over a collection of six films of the subgenre slasher produced between 1979 and 1984, from which performed was analysis in three steps aimed at mapping the clichés of fear found in the corpus. The thesis argues that the cliché movie is part of the institution as well, is the cinematic language and is composed from a certain degree of mobility. With regard to the logic that constitute the cliché of fear in horror movies slasher is evident the presence of the sublime in the 18 cliches found. They are organized in the form-content in order to establish a strong feature of appreciation of space - time uncertainty within the dramatic structure, highlighting the idea of threat.
Keywords: Cinema; Clichê; Narrativa; Terror; Estética audiovisual; Movie; Cliché; Narrativity; Horror; Visual aesthetics; ACCNPQ::Ciências Sociais Aplicadas::Comunicação